Use of biologic response modifiers for the management of ocular inflammatory conditions - Erick Rivera-Grana; Jay Siak; James T Rosenbaum (Indian Journal of Rheumatology)
Ocular inflammatory conditions can be challenging to manage due to their prolonged and complicated nature. While the mainstay treatment for most cases is oral or topical corticosteroids, it is very important that physicians know how other medications such as biologic response modifiers (biologics) could be used in certain cases. Through illustrative cases, we discuss how treatment with biologics can be helpful in the management of three challenging patients with ocular inflammatory conditions. We review and discuss, (1) a 60-year-old male with granulomatosis with polyangiitis and bilateral anterior scleritis who required rituximab; (2) a 25-year-old male with refractory, idiopathic, bilateral chronic panuveitis and retinal vasculitis, which was controlled with adalimumab after treatment failure with oral and topical corticosteroids, cyclosporine, and methotrexate; and (3) a 44-year-old female with unilateral blindness and juvenile psoriatic arthritis-related intermediate uveitis, who required adalimumab to control her complication of persistent macular edema. These cases highlight the considerations that are required when clinicians are faced with the need to commence biologic therapy for patients with refractory ocular inflammation.